A Persepsi Generasi Milenial Kota Waisai Terhadap Kawasan Konservasi Perairan Kabupaten Raja Ampat: Millennial Generation Perception Of Waisai District About Water Conservation Area The Raja Ampat Region - Gustiarini, Anastasia (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The Raja Ampat Water Conservation Area aims to protect and preserve biodiversity in the region, which is part of the Sea of the Head of the Birds of Papua. The Waisai District, the capital of Raja Ampat Regency, has the highest population of all the districts in Raja Ampat, with a population of 23,36 thousand people in 2023. The millennial generation has the highest percentage of 46% in the demographics of Raja Ampat District, making them an active audience segment in the country. The research method used in this study involved disseminating questionnaires using simple random sampling (SRS) to collect data from the millennial generation in Waisai City, India. The sample size was 10,057 people aged 20–44 in 2021. The study used the Slovin formula with a 90% confidence level. The total sample was 100 responden. The data was analyzed using Likert scale measurements, with each answer given a score. The assessment of respondents' interpretation of the conservation area perception was assessed using the index percentage formula. The conclusion of the discussion is that the Millennial Generation's perception of Raja Ampat Water Conservation Area is 58.47%, which falls within the criteria of “fair” or not fully understood. The results of the study showed that respondents' knowledge of conservation areas, both legislative, regulatory, territorial administrative boundaries, and zooning programs, was at a score below 60. Information on social media had a real impact on knowledge related to the status of the conservation area of Papua. The greatest perception score was about the four zonings on King Ampat's conservation status because many respondents were aware of it from various campaigns and socialization from various viewpoints.